Women’s Participation in the NREGA: Some Observations from Fieldwork in Himachal Pradesh, Kerala and Rajasthan - Ratna M. Sudarshan, Rina Bhattacharya and Grace Fernandez (IDS Bulletin, 2010)
The broad objective of this study was to understand the reasons behind the wide variations in participation by women in the NREGA and the policy implications that follow. Based on fieldwork in two states where women form a high proportion of the workers, Kerala and Rajasthan, and one where the proportion was low, Himachal Pradesh, emerging policy implications include the need to develop a wider range of activities that acknowledge life cycle issues and bodily ability; in sparsely populated and remote areas a different design or even a cash transfer programme may be better able to meet the objective of assuring minimum income; creation of spaces that allow non-governmental local groups to be participants in implementation and outreach work and not just watchdogs; immediate revision of the schedule of rates and implementing the revised rates to allow better earning, or else payment on a daily wage basis.